If No Moon - Linehan, Moira, 1945- (Book collections on Project MUSE., 2007)
If No Moon by award-winning author Moira Linehan documents the effects of profound loss and the dark withdrawal into grief. Wherever the author turns-the landscape of her backyard in Massachusetts, a Trappist monastery in Kentucky, the museums of Florence, or the cliffs of Inishmor in Ireland-she sees only the geography of emptiness. Crossovers between craft and art, form and voice, knitting and memory, recur throughout the poems. Lying within the tradition of narrative poetry, elegy, and the lyric, the collection reveals the mysterious journey of return. Coming full circle.